The impact of internal marketing on employee attitudes and behaviours in local public sector organisations - Ana Paula Rodrigues (Tourism & Management Studies)
The purpose of this paper is to extend the knowledge on the relationships between internal marketing (IM), job satisfaction, organisational commitment, organisational trust, and job performance, by proposing and testing a model describing the impact of IM on these employees’ attitudes and behaviours. The data collection was carried out using a questionnaire applied to employees of the Portuguese local public sector (namely the five Municipalities of Alto Tâmega region). A total of 565 valid questionnaires were obtained and treated using structural equation modelling. The results show that IM positively and directly influences job satisfaction, organisational commitment, and organisational trust, but do not directly influence job performance. Job performance is influenced by organisational commitment and organisational trust, but not by job satisfaction. However, the indirect effect of job satisfaction on job performance, mediated by organisational commitment and trust, is significant. In turn, job satisfaction directly influences organisational commitment, which, in turn, has a direct impact on organisational trust. To the best of the authors’ knowledge, this is the first time that a study of the relationship between IM and organisational trust has been conducted in the Portuguese local public sector context. Hopefully, the results obtained will significantly contribute to the development of the investigation of the effects of IM on this sector and to future research studies on internal marketing and public management.